Relationship of Economic Vulnerability With The Action of Criminal Violence on Household Women - Endang Tri Pratiwi; I K Dewi; LOD Abdullah; Ernawati Malik; Rudi Abdullah (International Journal of Management Progress, 2020)
From the description above, the conclusion in this study is basically there are five main causes that trigger the occurrence of domestic violence, namely economic difficulties, disobedience, bad behavior, jealousy, and others (child problems, the husband remarries, people's interference old/in-law). Some of the factors above which are the main factors in the occurrence of domestic violence are problems of economic vulnerability/difficulty. And the forms of domestic violence that are caused due to economic vulnerability problems, namely physical violence, psychological violence, sexual violence and neglect of the household.